Effects of mental and physical health on productivity - Ang, Angeline Jing Wen (Nanyang Technological University, 2022)
As physical and mental health impose a significant burden on people and reduce their productivity, this study aims to explore the correlation between the physical and mental health of individuals and their productivity. Utilising longitudinal data collected from the United States of America (USA) - Health and Retirement Study (HRS) and the Survey of Health, Ageing and Retirement in Europe (SHARE) within the time period of 1992 till 2020, we gathered 282,181 unique observations and measured their loss in productivity through the numbers of productive years lost (PYL). In the ten diseases we had identified, seven of them are physical health conditions (diabetes, cancer, high blood pressure (HBP), lung diseases, arthritis, heart diseases, and stroke) and the rest (depression, poor self-rated memory, and poor word recall score) are mental health conditions. Individually, the top three health conditions that had the greatest impact on PYL considering one’s demographics and behavioural patterns were lung diseases, stroke and depression. Furthermore, we also compared the effects of those who suffer from two physical health conditions against those with one physical and one mental health condition. We found that individuals with a combined chronic condition of both physical and mental health had a greater impact on PYL compared to those with two physical health conditions. As such, there is a need for individuals and employers to pay close attention to both physical and mental health conditions, of which mental health conditions have been shown to still be neglected in workplaces. This is vital to ensure that individuals can stay productive throughout the whole course of their employment career and minimise a fall in household income.